Parasocial Interaction Among Young Female Devotees of Korean Dramas - Bernadeta Meidy Setya Putri; Danny Irawan Yatim (ANIMA Indonesian Psychological Journal, 2019)
Korean drama is a media broadcast, which provides interactive parasocial experience to its enthusiasts, who actively seek out and involve themselves in it. The interactive parasocial process is divided into cognitive, affective, and behavioral sub-processes, producing “imagined interaction”. These shows have both positive and negative impacts upon their devotees; however, the way in which the parasocial interaction for the devotees of Korean dramas comes about is not yet well understood. A picture of this parasocial interaction for four young adult female devotees was obtained through interviews and journal entries. The participants used characters in Korean dramas as role models, and as parts of a learning process in their life transitions. They also used them as facilities for having social contacts, lessons about romantic relationships, and future career perspectives. Thematic analysis of this parasocial interaction produced a number of themes, these being the function of Korean dramas in the lives of devotees, “binge watching” as a recurrent parasocial interaction, and imaginings as romantic experiences. This research revealed that the cognitive sub-processes had a large part to play in the progress of parasocial interaction. It is recommended that further research be conducted into the impact of Korean dramas, as media products, upon Indonesian society.